KARAKTERISASI FISIKO KIMIA DAN INHIBISI Î±-GLUKOSIDASE BERAS ANALOG DARI BUAH Rhizophora mucronata [CHARACTERIZATION OF PHYSICO-CHEMICAL AND Î±-GLUKOSIDASE INHIBITION OF ANALOG RICE FROM Rhizophora mucronata FRUIT] - Hardoko, Hardoko; Alfiana, Devy; Puspitasari, Yunita E. (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2019)
This study aims to determine the physicochemical characteristics and Î±-glucosidase inhibition of analog rice from R. mucronata fruit flour, cassava flour, and E. cottonii flour. This research was conducted in April - October 2016. The experimental method was through the treatment ratio of R. mucronata fruit flour with cassava flour (60:40, 70:30, 80:20) and addition of E. cottonii flour (0, 3, 5, 7 %). Making analog rice using an extruder. The results showed that the treatment ratio of R. mucronata fruit flour with cassava flour and the addition of E. cottonii flour had a significant positive effect on Î±-glucosidase inhibition and physicochemical properties of rice. The higher the amount of R. mucronata fruit flour used the higher inhibition activity of Î±glucosidase and decrease the IC value. The best analog rice is made from R. mucronata 60% fruit flour, 40% cassava flour, and 5% E. cottonii seaweed flour. This rice has IC 50  value of 33.42 ppm, water content of 8.46%, food fiber content of 38.96%, red color (oHue value of 44.86), cooking time of 11.35 minutes, development volume of 135.09%, and starch content of 51.44%.   ABSTRAKPenelitian ini untuk mengetahui karakteristik fisiko kimia dan inhibisi Î±-glukosidase beras analog dari tepung buah R. mucronata, tepung singkong, dan tepung E. cottonii. Penelitian ini dilaksanakan pada bulan April - Oktober 2016. Metode eksperimen melalui perlakuan rasio tepungbuah R. mucronata dengan Tepung singkong (60:40, 70:30, 80:20) dan penambahan tepung E. cottonii (0, 3, 5, 7%). Pembuatan beras analog menggunakan extruder. Hasilnya menunjukkan bahwa perlakuan rasio tepung buah R. mucronata dengan tepung singkong dan penambahan tepung E. cottonii berpengaruh posistif nyata terhadap inhibisi Î±-glukosidase dan sifat fisiko kimia beras. Semakin tinggi jumlah tepung buah R. mucronata yang digunakan makin tinggi aktivitas inhibisi Î±glukosidase dan menurunkan nilai IC. Beras analog terbaik adalah yang terbuat dari tepung buah R. mucronata 60%, tepung singkong 40%, dan tepung rumput laut E. cottonii 5%. Beras ini mempunyai nilai IC 50, 33,42 ppm, kadar air 8,46%, kadar serat pangan 38,96%, berwarna merah (nilai o Hue 44,86), cooking time 11,35 menit, volume pengembangan 135,09%, dan kadar pati 51,44%. Kata Kunci : beras analog, Î±-glukosidase, IC50, R. mucronata